Cholesterol Granuloma in the Petrous Apex with Headache: a Case Report - Moreira, Francisco Leandro Fonteles; Almeida, Samara Pereira de; Feitosa, Yves Damon Gonçalves; Soares, Thayanne Karoline Coimbra; Ferreira, Bruzo Ralden Araújo; Cunha, Alessandra Alves Gomes; Sales, Nathália Denise Nogueira Peixe; Barreto, André Rodrigues Façanha; Tavora, Daniel Gurgel Fernandes; Soares, Diego Ximenes; Silveira, Cláudio Régis Sampaio; Paiva, Roberto Guido Santos (Headache Medicine, 2023)
Full abstract in PDF